Didactic strategies for the development of cultural identity in elementary education - Vargas Ortiz de Zevallos, Claudia Marcela (2014)
This research paper stemmed from a personal interest on the task of teachers regarding the development of their students’ cultural identity. The main purpose was to analyze the didactic strategies, planned by the elementary education teachers of an educational institution in San José de Moro – La Libertad (Peru), for the development of their students’ Mochica cultural identity from three planning elements: selection of contents, selection of educational materials, and schedule of activities. This research is exploratory and has a qualitative approach, based on a case study methodology. Among the most important results of the study, it is concluded that teachers indeed plan strategies that encourage the development of the Mochica cultural identity of their students in the areas of Personal and Social Education, Science and Environment, and Art. Nevertheless, the strategies planned to a greater extent are the ones which encourage knowledge acquisition and development of cognitive abilities.